2003
DOI: 10.1046/j.1365-2672.2003.01839.x
|View full text |Cite
|
Sign up to set email alerts
|

Employment of broad-range 16S rRNA PCR to detect aetiological agents of infection from clinical specimens in patients with acute meningitis - rapid separation of 16S rRNA PCR amplicons without the need for cloning

Abstract: Aims: The aim of this study was to develop a polyacrylamide gel electrophoresis (PAGE) method for the rapid separation of 16S rRNA PCR amplicons from aetiological agents of acute meningitis. Methods and Results: Blood samples from 40 patients with suspected acute meningococcal meningitis were examined for the presence of causal agents, including Neisseria meningitidis employing two methods: (i) broad-range 16S rRNA PCR in conjunction with PAGE and automated sequencing and (ii) species-specific PCR employing AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…The PCR is one of the most sensitive of such methods. Most PCR-based identifications in current clinical use rely on amplification of conserved genes, such as those encoding elongation factors (20) or RNA polymerase (rpoB) (6), or ribosomal DNA genes (10,26), followed by detection of species-specific sequences in the product (12,13). In some cases, species-specific genes, such as those encoding cytotoxins (4), can be amplified at the outset.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The PCR is one of the most sensitive of such methods. Most PCR-based identifications in current clinical use rely on amplification of conserved genes, such as those encoding elongation factors (20) or RNA polymerase (rpoB) (6), or ribosomal DNA genes (10,26), followed by detection of species-specific sequences in the product (12,13). In some cases, species-specific genes, such as those encoding cytotoxins (4), can be amplified at the outset.…”
mentioning
confidence: 99%
“…In some cases, species-specific genes, such as those encoding cytotoxins (4), can be amplified at the outset. Enhanced strategies include the use of multiplexing (14,26) or of highly parallel techniques, such as diagnostic DNA microarrays (5,8), to amplify and detect multiple sequences at once. Since each PCR primer can be considered a separate reagent, the quality control issues of such testing become more formidable with each additional gene target.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular techniques overcome some of the limitations of conventional culture under several clinical conditions (5)(6)(7)(8)(9)(10). Nevertheless, the role of molecular techniques in the diagnosis of VAP-RBSI remains unclear, and available approaches have not been extensively tested in the routine of a clinical microbiology laboratory.…”
mentioning
confidence: 99%
“…Schuurman et al [17], found broad range PCR was more useful in meningitis with sensitivity of 86%, specificity of 97%, positive predictive value of 80% and negative predictive value of 98% as compared to conventional culture. Xu et al [19], recommended use of highly resolving polyacrylamide matrix for separation of amplicons and digestion fragments. Thus, universal PCR followed by RFLP is an alternative, rapid, simple and effective method for detection of bacterial pathogens in CSF.…”
Section: Discussionmentioning
confidence: 99%